Le parlement roumain à l'épreuve du genre: les femmes politiques dans la législature 2004-2008 - Băluță, Ionela (2010)
Abstract: Women's low rate of participation at the highest levels of politics is a recurrent topic in the gender studies literature. Romanian historiography is not very generous in this regard. The present study proposes an introduction to a survey on the women politicians during the 2004-2008 legislature in Romania. In order to understand the complexity of structural, economic, political, and ideological factors, it is necessary to start with an analysis of the trajectories that allowed women to reach a high political position: a seat in the national Parliament. For this purpose, the article examines several types of sources (official CVs, personal blogs, as well as fragments from interviews conducted with 11 women members of Parliament during the 2004-2008 legislature) in order to address the following questions: Who are the women politicians during the 2004-2008 legislature? Which are the efficient resources for a successful political career? What is women politicians' subjective perspect